Capacitações tecnológicas do setor sucroenergético do Nordeste - Anjos, Kellyane Pereira dos (2012)
Until the 1990s, the sugar cane industry had a strong presence of the Government in its support. However, the government intervention not equalized disparities between the producing regions, thus regional differences were observed disadvantaging the Northeast. Since deregulation, producing units began to adopt different competitive strategies through new forms of organization and production management. This fact has been requiring from the companies adjustments in its basic skills and the development of new skills to operate in a changing environment permeated by new technology and new demands. In this context, this study aims to map the technological capabilities of the sugarcane agro-industry in the Northeast. Moreover, the mills/ distilleries were grouped according to its respective levels of technology through the method of cluster analysis. The results show that the sugar cane industry in the Northeast has high technological capabilities in basic and intermediate functions of investment, production/operations, innovation and relationship to the economy, however in the advanced level such capabilities are low or nonexistent. Thus, highlighting the fact that the region needs to develop its technological capabilities in order to survive nationally.